2015
DOI: 10.1161/circulationaha.115.015371
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Changes in Left Ventricular Function After Aortic Valve Replacement

Abstract: Background-Our objectives were to identify correlates of mortality and congestive heart failure after aortic valve replacement (AVR) according to preoperative left ventricular (LV) function and to describe the incidence, time course, and correlates of LV recovery and mass regression postoperatively. Methods and Results-A total of 3112 patients with AVR were assessed in a follow-up clinic with echocardiography (median follow-up, 6.0 years). At operation, their mean age was 67.8±13.4 years, one third were female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 24 publications
4
50
0
1
Order By: Relevance
“…Progressive myocardial hypertrophy causes fibrosis and myocyte degeneration, which contribute significantly to LV dysfunction 16. Several studies have demonstrated that persistent LV hypertrophy after SAVR is associated with worse clinical outcome and mortality,1 2 17 and regression of LV hypertrophy has been related to improved survival rates,1 as well as lower risk of myocardial infarction and stroke 18 19. Moreover, in patients who underwent SAVR for AS, postoperative RAS blockade therapy with ACE inhibitors or ARBs was associated with augmented regression of LV hypertrophy,4 20 as well as increased survival rates 6.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive myocardial hypertrophy causes fibrosis and myocyte degeneration, which contribute significantly to LV dysfunction 16. Several studies have demonstrated that persistent LV hypertrophy after SAVR is associated with worse clinical outcome and mortality,1 2 17 and regression of LV hypertrophy has been related to improved survival rates,1 as well as lower risk of myocardial infarction and stroke 18 19. Moreover, in patients who underwent SAVR for AS, postoperative RAS blockade therapy with ACE inhibitors or ARBs was associated with augmented regression of LV hypertrophy,4 20 as well as increased survival rates 6.…”
Section: Discussionmentioning
confidence: 99%
“…LV remodelling alone can greatly impact morbidity in this patient population. 17,18 TAVR causes an acute decrease in the transvalvular gradient that could lead to unloading the LV and, thus reverses LV remodelling and improves clinical outcomes. 18 Previous studies have suggested that female sex is associated with better mid-and long-term survival post-TAVR despite the increased rate of periprocedural complications.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 TAVR causes an acute decrease in the transvalvular gradient that could lead to unloading the LV and, thus reverses LV remodelling and improves clinical outcomes. 18 Previous studies have suggested that female sex is associated with better mid-and long-term survival post-TAVR despite the increased rate of periprocedural complications. [2][3][4][5][6] There is currently no clear-cut explanation for why women fare better than men after TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…6 Severity of coexisting coronary artery disease was associated with impaired clinical outcomes at 1 year after TAVR in 445 patients with severe AS (mean age, 82.5 years; 56% female). 7 Severe AS and left ventricular ejection fraction of <50% with or without aortic valve replacement, 8,9 low-flow, low-gradient AS with reduced stroke volume index, [10][11][12][13] and reduced global longitudinal strain by speckle-tracking echocardiography 14 have increased risk of mortality after sAVR or TAVR in patients with severe AS. Midwall myocardial fibrosis that can be detected by late gadolinium enhancement, 15 and prosthesispatient mismatch 16,17 have also been reported as prognosticators in patients with severe AS after sAVR or TAVR.…”
Section: See Article By Treibel Et Almentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] The coexistence of wtATTR and severe AS may cause severe hypertrophy and left ventricular functional impairment, which can be misdiagnosed as low-flow, low-gradient severe AS. [10][11][12][13] Recent studies have suggested that patients with wtATTR are characterized by lower left ventricular ejection fraction, stroke volume index, left ventricular basal, and midradial strains compared with age and wall thickness matched mutant ATTR patients.…”
Section: See Article By Treibel Et Almentioning
confidence: 99%